Operation of Automated Rubber Tyred Gantry (ARTG) in Supporting Container Receiving Operations to Minimize Truck Turn Round Time (TRT) - Fajar Transelasi; Shaula Anggraini Seco; Heri Prasetyo (Postgraduate, University of Mataram, 2025)
This study investigates the impact of the Automated Rubber Tyred Gantry (ARTG) system on terminal operations at Semarang Container Terminal, with the specific aim of assessing its contribution to efficiency while identifying operational challenges. A qualitative descriptive approach was applied, using field observations, interviews, and document analysis. The findings indicate that ARTG automation enhances container handling efficiency, particularly by reducing truck Turn Round Time (TRT) and minimizing handling errors. The system’s advanced features, such as sensors, GPS, and cameras, enabled more precise and reliable container transfers. However, challenges were also identified, including technical malfunctions, weather disturbances, and occasional system failures that disrupted operations and increased TRT. These results suggest that while ARTG significantly improves operational performance, its effectiveness depends on addressing recurring disruptions. Ensuring routine maintenance, timely system upgrades, and operator readiness is critical to sustaining system reliability. In conclusion, the study demonstrates that ARTG provides measurable efficiency gains in container terminal operations, yet its optimal performance requires continuous technical support and proactive problem management. These insights contribute to advancing automation practices in port operations and strengthening competitiveness in the maritime industry.